Clinical and pathological characteristics and hormone receptor status of women with breast cancer in the European Gaza Hospital: a retrospective chart-based review. (July 2021) - Musallam, Rami; Alnajjar, Mohammed; Al-Shurafa, Ahmad; Bottcher, Bettina
Abstract: Background: Breast cancer is the most common cancer (accounting for 31·3% of all cancers) among women in the Gaza Strip. This audit examines clinical and pathological characteristics of women presenting with breast carcinoma to the European Gaza Hospital (EGH), a governmental hospital and oncological centre serving 600 000 people in the southern Gaza Strip. Methods: Data were collected from the records of patients with breast cancer treated at the EGH from March, 2015, to Sept, 2017. 397 cases were identified, including 218 patients with full hormone receptor status (oestrogen, progesterone, and Her2/neu receptor status). Data were analysed using Student's t test. Findings: The mean age was 54 years (SD 11·2). 64% of the women (139 of 218) were older than 50 years, and 16% (33 of 218) were younger than 40 years. Histological grade was assessed for 56% of the women (122 of 218), and 55% of these women (67 of 122) presented with grade II tumours. Tumour size was documented in 82% of the files (178 of 218), and tumours were 2–5 cm in 47% of the documented cases (83 of 178). Furthermore, 51% of women (112 of 218) tested positive for the presence of cancer cells in lymph nodes, and 6% (14 of 218) had distant metastasis at presentation. The clinical stage at diagnosis was recorded in 56% of cases (122 of 218), of whom 4% (five of 122) presented at stage I, 54% (66 of 122) presented at stage II, and 42% (51 of 122) presented at stage III/IV. Pre-operative histopathology was carried out for 120 women, of whom 85% (102 of 120) had intraductal carcinoma. Only 81% of women (177 of 218) had post-operative histopathology, of whom 79% (139 of 177) had intraductal carcinoma. The histopathological type was significantly different for pre-operative and post-operative specimens (p<0·0001). Oestrogen receptor status was positive in 58% of patients (127 of 218), progesterone receptor status was positive in 57% of patients (124), and HER2/neu receptor was overexpressed in 33% of patients (65). Triple-negative breast cancer (testing negative for oestrogen, progesterone, and HER2/neu) was found in 23% of the women (49) and double-negative breast cancer (testing negative for oestrogen and progesterone but positive for HER2) in 11% of the women (24). Interpretation: Patients with breast cancer present with advanced disease in the Gaza Strip. HER2/neu overexpression was approximately 10% higher than the percentages reported in the literature for the USA. The significant difference between pre-operative and post-operative specimens' histopathological type could be due to use of fine-needle aspiration. Guidance from the Royal College of Radiologists recommends pre-operative core biopsy. It should be noted that documentation in the patient medical files was incomplete, which is a common obstacle in Gaza that must be tackled for effective improvement in the quality of care. Funding: None.